462 IUGR ALTERS EPIGENETIC REGULATION OF HEPATIC DUSP5. (1st January 2005) - Fu, Q.; McKnight, R.; Yu, X.; Wang, L.; Lane, R.
Abstract : Background: Insulin resistance and dyslipidemia characterize rats rendered IUGR through uteroplacental insufficiency. IUGR changes the acetylation profile of specific lysines on histone H3 (H3). These changes physically associate with genes whose mRNA levels are persistently altered in IUGR liver. Objective: Chromatin immunoprecipitation (ChIP) is a technique that identifies regions of DNA which are in contact with acetylated histones. We therefore hypothesized that we could identify candidate genes whose expression will be persistently altered through ChIP and differential display PCR. Design/Methods: Both uterine arteries were ligated on d19 in pregnant Sprague-Dawley rats. Liver was harvested from IUGR and sham controls on d0, d21 and d120. Chromatin was immunoprecipitated with anti-H3 (acetyl lys 9). DNA purified from ChIP-chromatin was amplified by PCR with CpG rich primers and analyzed by differential display. DNA bands differentially represented between sham and IUGR were cloned and sequenced. mRNA levels of candidate genes isolated from the ChIP/differential display screen were analyzed using real-time RT-PCR. Hepatic genomic DNA CpG methylation state of each clone was examined using the bisulfite method. Results: ChIP/differential display demonstrated that IUGR affected the DNA-histone contacts of the MAPK phosphatase DUSP5 gene. This finding was associated with a persistent and significant decrease in DUSP5 hepatic mRNA levels in d0 pups (73.5 [138